Consumer search and oligopolistic pricing : an empirical investigation - Maarten C. W. Janssen; José Luis Moraga-González; Matthijs R. Wildenbeest (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper presents an empirical examination of oligopoly pricing and consumer search. The theoretical model allows for sequential and non-sequential search and, using the theoretical restrictions firm and consumer behavior impose on the data, we study the empirical validity of the models. Two equilibria arise: one with costless search and the other with costly search. We find that the costless search equilibrium works well for products with a relatively low value, and, by implication, a small number of sellers. By contrast, the costly search equilibrium explains the observed data in a manner that is consistent with the underlying theoretical model for almost all products (for 86 out of 87!).
Keywords: D83; D40; L13; C13; 330; consumer search; oligopoly; price dispersion; maximum likelihood estimation; Konsumentenverhalten; Informationskosten; Suchtheorie; Oligopol; Theorie